(3ebGdI aj GdgfOHGs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf gPg QSGdI GedGAgG GdTjN GdQFjS ai GdYdI GdJi dGLdgG fgi GdCWHGA Yf ZSd GdgfOjG s
(3BNQgG (B:s
(3dCfg EPG JbOe Edi eG JQcg GdZSd ai LhgQ GdgfOHG hai HGWfg ef Jdc GdbhI ajMddg hfLQg abO HGf GdUhGH JeJ GdebGdI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B900s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs